Histopathological study of skin tumours - Dr. Matariswa Samanta; Dr. Nitesh Mangal; Dr. K. Bhavani; Dr. G. Koteeswaran; Dr. Piyushkumar C Parmar (Tropical Journal of Pathology and Microbiology, 2018)
Background: Skin tumour and their various histological typesalways creating a diagnostic difficulty. Histopathology is the gold standard for diagnosis in turn is used by clinicians to aid clinical outcome andalso emphasizing certain key forvaluable observation of certain tumours. Objectives: The study was conducted to find out the occurrence of different tumours of skin in MGMCRI and to classify skin tumours (WHO classification). Methods: The pathological features of 52 cases of Skin Tumours were analysed between May 2009 and May 2014. Section of skin tissue was studied by light microscopy after hematoxylin and eosin staining. Results: A total number of 52 cases of skin tumours were studied. Benign skin tumours constituted 44.23% while malignant skin tumours constituted 55.76% of all skin tumours. Intradermal nevus was the most common benign Skin tumours while Squamous Cell Carcinoma was the most common malignant tumours. Conclusion: Light Microscopic examination remains the standard technique for the diagnosis of the tumours. Although special stain and immunochemistry can be utilised in situation where the diagnosis cannot be confirmed on hematoxylin and eosin.